Inflammatory Biomarkers for Children with Sleep Disorders: A Review - Prabhu, Nagashree; Shetty, Vabitha (Journal of Health and Allied Sciences NU, 2022)
Introduction Obstructive sleep apnea (OSA) syndrome is a highly prevalent problem in children. Unfortunately sleep disorders in children remain largely unreported and underdiagnosed due to various reasons. Overnight in-laboratory polysomnography (PSG) is the gold standard diagnostic method for OSA; however, it has several drawbacks. Hence there is a need for simple alternative diagnostic methods, such as biomarkers. Children with OSA seem to have an inflammatory aspect to its pathophysiology; thus the rationale for evaluating inflammatory biomarkers.Objective This narrative review aimed to evaluate the existing knowledge regarding inflammatory biomarkers for children with sleep disorders.Materials and Methods An extensive search of all literature linked to the topic was performed in PubMed, Medline, EBSCOhost, Cochrane library database CENTRAL, and Google Scholar search engine. Keywords used in the search included combinations of the following: inflammation, sleep disorders, children, and biomarkers. Studies in the list of references of relevant literature were also included. A total of 155 articles published in the period from 1997 to 2021 were initially included in this review. Selected articles comprised original research, meta-analysis, and systematic reviews.Results Studies have mainly centered their investigations on serum inflammatory biomarkers, namely interleukin-6, tumor necrosis factor-α, and C-reactive protein. Very few studies investigated salivary inflammatory biomarkers in children.Conclusion Evidence suggests that children with sleep disorders have elevated levels of salivary as well as serum inflammatory biomarkers in comparison to normal healthy children. Also increased levels of these biomarkers correlate with disease severity. However, more studies are needed to determine the sensitivity and specificity of salivary inflammatory biomarkers for children with sleep disorders.
Keywords: inflammation; sleep disorders; children; biomarkers